Standards of Care: Management of Patients with Nonvariceal Upper Gastrointestinal Hemorrhage - Guido Van Rosendaal (Canadian Journal of Gastroenterology)
This article is the outcome of a formal process of clinical guideline development involving 25 participants with expertise covering a wide range of disciplines and nationalities, as well as nonvoting observers representing Health Canada and seven industry sponsors. Twenty recommendations are presented, each specifying the degree of support and dissention expressed in the panel's votes. One hundred ninety-two references are cited. Early endoscopy and risk stratification are central strategies in the framework provided.